Disability Laws in India - Dr. Manpreet Dhanoa (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
Disability is a complex social issue and it is increasingly becoming a major concern all over the world. The number of disabled people is increasing across the world due to various reasons. Disabled people comprise a significant minority in most countries and their number also constitutes one of the largest minorities in the world. Traditionally, disability has long been considered to be an index of marginality. They faced direct and indirect discrimination and were not able to enjoy the full spectrum of civil, political, social, cultural and economic rights.